Assessment of social impacts of a reservoir on a saline soil area in northeast thailand - Sirkaew, Uba; Seeboonruang, Uma (My University, 2013)
Although useful in flood prevention and as the source of water for irrigation and consumption, reservoirs could nevertheless not merely create negative social impacts for those living near them but also wreak havoc on the environment following their construction. These environmental and social impacts should be addressed especially in the Northeastern part of Thailand where their history revolving in salt mines and traditional salt production. The attitude questionnaires were used in this study to assess the impacts of a reservoir operation in a saline soil area on the social changes in 8 aspects. It was found, based on more than 160 replied questionnaires, that even if most respondents saw that the reservoir improved their standard of living in several aspects, a number of the respondents expressed concerns that their traditional way of life and ancient salt production method were disappearing. These people did express their concerns for their own safety, their worries about their community future, and hopes for better future of their own and that of their children. © (2013) Trans Tech Publications, Switzerland.
Keywords: Environment; Reservoir; Saline soil; Social impact assessment